2023
DOI: 10.1111/aos.15793
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the prevalence of uveitis between Crohn's disease and ulcerative colitis: A systematic review and meta‐analysis

Haowen Lin,
Jiaqing Zhang,
Chen Liang
et al.

Abstract: PurposeUveitis is one of the ocular manifestations of inflammatory bowel disease (IBD) that is often overlooked and has been considered a sign of severe IBD. As typical subtypes of IBD, differences exist in the prevalence of uveitis between Crohn's disease (CD) and ulcerative colitis (UC). Our study systematically assessed differences in the prevalence of uveitis between CD and UC.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines were used. We performed a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A recent systematic review and meta-analyses reported an uveitis prevalence of 2.38% in IBD patients. Uveitis was statistically significantly more prevalent in CD (3.27%) than in UC patients (1.60%, p < 0.05) [17,61]. While CU's activity and uveitis do not correlate, uveitis is much more frequent and persistent during CD flares [62].…”
Section: Uveitismentioning
confidence: 91%
“…A recent systematic review and meta-analyses reported an uveitis prevalence of 2.38% in IBD patients. Uveitis was statistically significantly more prevalent in CD (3.27%) than in UC patients (1.60%, p < 0.05) [17,61]. While CU's activity and uveitis do not correlate, uveitis is much more frequent and persistent during CD flares [62].…”
Section: Uveitismentioning
confidence: 91%